1999
DOI: 10.1128/aem.65.7.3056-3063.1999
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated with Anaerobic Benzene Degradation in a Petroleum-Contaminated Aquifer

Abstract: Microbial community composition associated with benzene oxidation under in situ Fe(III)-reducing conditions in a petroleum-contaminated aquifer located in Bemidji, Minn., was investigated. Community structure associated with benzene degradation was compared to sediment communities that did not anaerobically oxidize benzene which were obtained from two adjacent Fe(III)-reducing sites and from methanogenic and uncontaminated zones. Denaturing gradient gel electrophoresis of 16S rDNA sequences amplified with bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
121
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(130 citation statements)
references
References 49 publications
5
121
1
3
Order By: Relevance
“…For aerobic degradation of benzene well studied pathways are known (Gibson et al, 1968). Furthermore, enrichment cultures and microcosm studies indicated that benzene can be effectively degraded in the absence of molecular oxygen under iron-reducing (Lovley et al, 1996;Anderson et al, 1998;Rooney-Varga et al, 1999;Kunapuli et al, 2008), sulfate-reducing (Lovley et al, 1995;Kazumi et al, 1997;Phelps et al, 1998;Caldwell and Suflita, 2000;Abu Laban et al, 2009), denitrifying (Burland and Edwards, 1999;Coates et al, 2001;Ulrich and Edwards, 2003) and methanogenic (Ulrich and Edwards, 2003;Chang et al, 2005) conditions. So far, only two anaerobic benzene-degrading strains were isolated to purity, which were described as denitrifying members of the genera Dechloromonas and Azoarcus (Coates et al, 2001;Kasai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For aerobic degradation of benzene well studied pathways are known (Gibson et al, 1968). Furthermore, enrichment cultures and microcosm studies indicated that benzene can be effectively degraded in the absence of molecular oxygen under iron-reducing (Lovley et al, 1996;Anderson et al, 1998;Rooney-Varga et al, 1999;Kunapuli et al, 2008), sulfate-reducing (Lovley et al, 1995;Kazumi et al, 1997;Phelps et al, 1998;Caldwell and Suflita, 2000;Abu Laban et al, 2009), denitrifying (Burland and Edwards, 1999;Coates et al, 2001;Ulrich and Edwards, 2003) and methanogenic (Ulrich and Edwards, 2003;Chang et al, 2005) conditions. So far, only two anaerobic benzene-degrading strains were isolated to purity, which were described as denitrifying members of the genera Dechloromonas and Azoarcus (Coates et al, 2001;Kasai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analyses of microbial communities have indicated that Geobacter species are the predominant metal-reducing microorganisms in various subsurface sediments in which dissimilatory metal reduction is an important process (Rooney-Varga et al, 1999;Holmes et al, 2002;Anderson et al, 2003;Roling et al, 2003;North et al, 2004;Vrionis et al, 2005). One of the hallmark features of Geobacter species is their abundant c-type cytochromes.…”
Section: Introductionmentioning
confidence: 99%
“…Still, benzene in anoxic surroundings is apparently less readily degraded than its alkylated derivatives; anaerobic degradation of the latter, in particular of toluene, has thus been studied more frequently and in much more detail (Heider, 2007). Anaerobic degradation of benzene was demonstrated under conditions of nitrate reduction (Burland and Edwards, 1999;Ulrich et al, 2005), iron(III) reduction (Anderson et al, 1998;Rooney-Varga et al, 1999), sulfate reduction (Lovley et al, 1995;Phelps et al, 1996;Kazumi et al, 1997;Caldwell and Suflita, 2000) or methanogenesis (Grbić-Galić and Vogel, 1987;Ulrich and Edwards, 2003), either in situ, in laboratory microcosms or in enrichment cultures. Only few pure cultures were reported to utilize benzene anaerobically.…”
Section: Introductionmentioning
confidence: 99%